EFL UNIVERSITY STUDENTS’ PRACTICES AND PERCEIVED BENEFITS OF REFLECTIVE LEARNING - Inaayah, Athiyyah; Fithriani, Rahmah (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
Critical thinking helps students analyze information thoroughly and identify relevant information for themselves. Students are encouraged to think critically about their studies, which can be achieved through reflective learning. This study aims to understand the students' perceptions of reflective learning and how the students practice it in the class, especially in higher students. This research was done by using a qualitative, descriptive case study approach, the participants were 33 students and the participants for the interview were four women and two men enrolled in an Indonesian university from the English Education Department in the seventh semester and the same class. It can be concluded that the responses to the questionnaire are affirmative, supporting the practices and having a good perception of reflective learning. The practices of reflective learning that the students ever faced in the class are text diary and learning log. Reflective learning gives some benefits to the students such as building critical thinking and helping the students to prepare themselves.